Performance Improvement Model Through Task Commitment as Intervening - Yulina, Yulina Eliza; Suheri, Suheri; Andria , Yass (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
The purpose of this researchto test empirically how the influence of work culture, organizational support and task commitment to performance directly and indirectly.The study involved as many as 49 respondents to civil servants who worked at the Community and Village Empowerment Service of West Sumatra Province. This research was conducted using probability sampling and proportionate stratified random sampling techniques.Data processing using SPSS with Path Analysis. The results of this study indicate that work culture has a significant effect on employee performance; Organizational Support has a significant effect on Employee Performance; Work Culture has a significant effect on Employee Task Commitment; Organizational Support has no significant effect on Employee Task Commitment; Task Commitment has a significant effect on Employee Performance;Task Commitment as an intervening variable gives influence between Work Culture and Employee Performance; Task Commitment as an intervening variable has no effect between Organizational Support and Employee Performance